2017
DOI: 10.1002/2017gl074778
|View full text |Cite
|
Sign up to set email alerts
|

Driving Roles of Tropospheric and Stratospheric Thermal Anomalies in Intensification and Persistence of the Arctic Superstorm in 2012

Abstract: Intense synoptic‐scale storms have been more frequently observed over the Arctic during recent years. Specifically, a superstorm hit the Arctic Ocean in August 2012 and preceded a new record low Arctic sea ice extent. In this study, the major physical processes responsible for the storm's intensification and persistence are explored through a series of numerical modeling experiments with the Weather Research and Forecasting model. It is found that thermal anomalies in troposphere as well as lower stratosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Consistent with the findings of Yamagami et al (2018a), Yamazaki et al (2015) found that assimilation of additional radiosonde observations was crucial for accurate forecasts of this cyclone. Tao et al (2017a) also found that a polar vortex was important for the intensification of this cyclone, specifically through its role in intensifying the upper-tropospheric jet. A similarly exceptional Arctic cyclone developed in 2016, lasting for more than 1 month.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistent with the findings of Yamagami et al (2018a), Yamazaki et al (2015) found that assimilation of additional radiosonde observations was crucial for accurate forecasts of this cyclone. Tao et al (2017a) also found that a polar vortex was important for the intensification of this cyclone, specifically through its role in intensifying the upper-tropospheric jet. A similarly exceptional Arctic cyclone developed in 2016, lasting for more than 1 month.…”
Section: Introductionmentioning
confidence: 83%
“…An ongoing World Meteorological Organization World Weather Research Programme (the Polar Prediction Project) was developed in recognition of the importance of improved weather and environmental prediction services for the polar regions. The mesoscale to synoptic-scale tropopause-based coherent vortices (called tropopause polar vortices, TPVs) frequently observed in polar regions (Hakim and Canavan, 2005;Cavallo and Hakim, 2009) are hypothesised to play a central role in Arctic cyclone genesis and intensification (Tao et al, 2017a;Yamagami et al, 2017Yamagami et al, , 2018a. In this paper we present a climatology of summer Arctic cyclones and TPVs by tracking features in the latest global reanalysis of the European Centre for Medium-Range Weather Forecasts (ECMWF), ERA5, and deduce the role of TPVs in the initiation, intensification and structure of Arctic cyclones.…”
Section: Introductionmentioning
confidence: 99%
“…Intense and long-lasting storms have more frequently occurred over the Arctic Ocean, which have obviously caused or contributed to the occurrence of extreme events, including record lows of sea-ice extents in summer and record highs of warm temperature in winters [24][25][26][27][28]. To understand intense and long-lasting storms and identify sources of their predictability, detailed observational and modeling studies have revealed that these Arctic storms have demonstrated unique dynamic and thermodynamic structures and driving mechanisms [19,20,22,23], different from their midlatitude counterpart [52].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In addition to the impacts of the large-scale atmospheric circulation forcing, synoptic scale Arctic storm activities have also demonstrated substantial influences on various aspects of Arctic sea ice properties and surface climate [8,[16][17][18]. In particular, intense and long-lasting storms have more frequently occurred over the Arctic Ocean during recent decades [19][20][21][22][23]. They have obviously caused or contributed to the observed extreme events, such as the record minima of summer sea ice extent in 2012 and 2016 and the record maxima of winter surface air temperature in 2015/2016 and 2017/2018 [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the findings of Yamagami et al (2018a), Yamazaki et al (2015) found that assimilation of additional radiosonde observations was crucial for accurate forecasts of this cyclone. Tao et al (2017) also found that a polar vortex was important for the intensification of this cyclone, specifically through its role in intensifying the upper-tropospheric jet. A similarly exceptional Arctic cyclone developed in 2016, lasting for more than one month.…”
mentioning
confidence: 83%